2021
DOI: 10.1101/2021.08.30.21262844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of mental health and substance use issues on COVID-19 vaccine readiness: a cross sectional community-based survey in Ontario, Canada

Abstract: Background: COVID-19 vaccines have been approved for use in Canada since December 2020. However, data about factors associated with vaccine hesitancy and the impact of mental health and/or substance use (MHSU) issues on vaccine uptake are currently not available. The goal of this study was to explore factors, particularly MHSU factors, that impact COVID-19 vaccination intentions in Ontario, Canada. Methods: A community-based cross-sectional survey with recruitment based on age, gender, and geographical locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…This study found that vaccine hesitancy was significantly associated with gender, employment status, and education. Among our participants, females are more hesitant about receiving the COVID-19 vaccine, which is in line with previous studies in China and abroad [ 23 , 24 , 25 , 26 ]. It might be explained that women are more concerned with the side effects and have a higher chance of having medical contraindications, such as during pregnancy and breastfeeding [ 23 , 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study found that vaccine hesitancy was significantly associated with gender, employment status, and education. Among our participants, females are more hesitant about receiving the COVID-19 vaccine, which is in line with previous studies in China and abroad [ 23 , 24 , 25 , 26 ]. It might be explained that women are more concerned with the side effects and have a higher chance of having medical contraindications, such as during pregnancy and breastfeeding [ 23 , 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…Among our participants, females are more hesitant about receiving the COVID-19 vaccine, which is in line with previous studies in China and abroad [ 23 , 24 , 25 , 26 ]. It might be explained that women are more concerned with the side effects and have a higher chance of having medical contraindications, such as during pregnancy and breastfeeding [ 23 , 24 , 25 , 26 ]. In addition, a higher education level was associated with higher vaccine hesitancy levels, which is supported by the previous literature [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Though our findings did not uncover demographic trends among vaccine hesitancy, our research may deepen the understanding gained from previous quantitative studies that do break down demographic predictors. For example, one study from Ontario found that being Black, being a woman, having lower levels of income and education, and being younger were all factors that increased the likelihood of being vaccine-hesitant or resistant [ 48 ]. Taken together, these data and our results show that community divides may fall along specific demographic characteristics or have implications for some groups over others.…”
Section: Discussionmentioning
confidence: 99%